Seeking refuge: a study on children’s rights approach to international refugee law - Sahay, Nidhi (The University of Edinburgh, 2025)
This thesis examines whether the element of ‘persecution’ as provided in the definition of refugee set out in the 1951 Refugee Convention can be interpreted in a manner that recognises the refugee qualification claims of children based on the violation of their substantive rights recognised in the 1989 United Nations Convention on the Rights of the Child (UNCRC). This research has been undertaken in the backdrop of the fact that nearly 40 per cent of all forcibly displaced people are children and this number is only increasing. Despite the magnitude of this tragedy, the definition of refugee is age-neutral and does not specifically account for a child’s evolving capacities, individuality, or the unique nature of her experiences and forms of oppression. This anomaly has arisen from the fact that when the Refugee Convention was adopted, children were seen merely as objects of welfare and paternalistic protection and not as bearers of rights. It was nearly four decades later that the right of children, along with their evolving capacities to exercise those rights, were recognised under the UNCRC. The UNCRC, while upholding the rights of refugee children to be treated on par with domestic children, failed to address the issue of their qualification as refugees. This created a gap in the protection of asylum seeking children both under the Refugee Convention and the UNCRC. To ensure that the refugee status determination of children takes into account the child-specific forms and manifestations of persecution, this thesis advocates an evolutionary interpretation of the refugee definition through the lens of children’s rights as provided under the UNCRC. This is realised by firstly applying the rule of treaty interpretation as provided under the 1969 Vienna Convention on the Law of Treaties to build the conceptual foundations for adopting a children’s rights approach towards the interpretation of the refugee definition. This exercise establishes that the UNCRC can be regarded as a relevant rule of international law applicable in the relations between the parties and should be taken into account when interpreting the refugee definition in the context of refugee status determination of children. Thereafter, the policy, guidelines, and jurisprudence generated by the UNHCR, the CRC Committee and a selection of States are examined and reviewed to ascertain the extent to which the rights of children are influencing the refugee status determination of children in practice. The survey of jurisprudence is limited to Canada, New Zealand, UK, USA, and Australia because they have an established and robust national refugee status determination system with long standing jurisprudence on refugee law cases. The review of case law shows that the decision making authorities are increasingly taking the violation of children’s rights into account while undertaking refugee status determination of children. Thereby establishing that recourse to the children’s rights approach in the refugee status determination and interpretation of the refugee definition is no longer an anomaly but is increasingly becoming a part of the adjudication process and policy concerning children on the move. While no one single interpretative solution alone can effectively address the protective needs of refugee children, the children’s rights approach advocated in this thesis provides a feasible solution for the determination of refugee status of children by taking into account the violation of their rights as provided under the UNCRC.
Keywords: Children's Rights; Persecution; 1951 Refugee Convention; UNCRC (United Nations Convention on the Rights of the Child); Refugee Status Determination